Response to Millet et al - Gattoni, C.; Marcora, S. M. (International Journal of Sports Physiology and Performance, 2022)
Rsponse to Millet et al: Comment on Gattoni et al: Sleep Deprivation Training as a Highway to Hell in Ultratrail (SPONET-ID 4078222), Gattoni et al: Sleep deprivation training to reduce the negative effects of sleep loss on endurance performance: a single case study (SPONET-ID 4074380)